Relationship between the social participation and social skills of pupils with an intellectual disability: A study in inclusive classrooms - Garrote, Ariana (Frontline Learning Research, 2017)
Researchers claim that a lack of social skills might be the main reason why pupils with special educational needs (SEN) in inclusive classrooms often experience difficulties in social participation. However, studies that support this assumption are scarce, and none include pupils with intellectual disability (ID). This article seeks to make an important contribution to this discussion. The social skills and social participation of pupils with ID and their typically developing (TD) peers in 38 general education classrooms were assessed with multidimensional instruments. The analyses indicate that the majority of pupils with ID were not popular but were socially accepted and had friends. Additionally, no significant relationship was found between social skills and the social participation of pupils with ID, although such pupils had lower levels of social skills compared with their TD peers. Thus, it appears that pupils with ID do not require high levels of social skills to be befriended or accepted by classmates. In contrast, social skills were associated with popularity and social acceptance within the group of TD pupils. In fact, popular TD pupils had the highest level of social skills. These findings support the assumption that in addition to low levels of social skills, there must be other mechanisms that influence the social participation of pupils with an ID in inclusive classrooms.